Prioritized solutions for overcoming barriers when implementing lean in the healthcare supply chain: A Saudi perspective - Abdulaziz M. Almutairi; Mohammed Almanei; Ahmed Al-Ashaab; Konstantinos Salonitis (Logistics, 2021)
The main purpose of this paper is to propose solutions for overcoming the obstacles that healthcare organizations might face when implementing lean. An in-depth review of existing barriers for lean implementation in healthcare supply chain is presented and validated by experts. Although there is a widespread use of lean concepts in developed countries, little attention has been paid to implementing a lean approach by healthcare providers in developing countries. The present study's key novelty and contribution is related to this research gap. The study is thus focused in proposing solutions for healthcare organisations in developing countries, especially in Saudi Arabia. The efficacy of these solutions is assessed through experts' opinion. The paper enhances the body of knowledge for the successful implementation of lean in a hospital setting.
Keywords: 650; barriers; developing countries; health sector; lean implementation